04 2logeqns

Logarithmic equations

We can solve logarithmic equations by rewriting them in index form.
.

Example 1

Solve for x:
a)$\log_2(2x-1)=4$

b)$\log_3(3x+1)=0$

c)$\log_3 \big(\frac{1}{9}\big)=x$

Solution:

a)$\log_2(2x-1)=4 \;\; \iff \;\; 2^4=2x-1$

… … … … $2x-1=16$

… … … … $2x=17$

… … … … $x=\dfrac{17}{2}$
.

b)$\log_3(3x+1)=0 \;\; \iff \;\; 3^0=3x+1$

… … … … $3x+1=1$

… … … … $3x=0$

… … … … $x=0$
.

c)$\log_3 \big(\frac{1}{9}\big)=x \;\; \iff \;\; 3^x=\frac{1}{9}$

… … … … $3^x=\dfrac{1}{3^2}$

… … … … $3^x=3^{-2}$

… … … … $x=-2$

.

Example 2

Solve for x: $\log_x(27)=\frac{3}{2}$

Solution:

… … $\log_x(27)=\frac{3}{2} \iff x^{\frac{3}{2}}=27$

… … $x^{\frac{3}{2}}=3^3$

… … $\big(x^{\frac{1}{2}}\big)^3=3^3$

… … $x^{\frac{1}{2}}=3$

… … square both sides

… … $x=9$

.

Example 3

Use the calculator to find x correct to 3 decimal places.

… … $\log_x(5)=3$

Solution:

04.2eg3.gif

… … $x = 1.710$

.

Example 4

Solve for x: $\log_2(x-1) + \log_2(x+2) = \log_2(6x-8)$

Solution:

… … $\log_2(x-1)+ \log_2(x+2)= \log_2(6x-8)$

… … Use log laws to combine left side of the equation

… … $\log_2(x-1)(x+2)= \log_2(6x-8)$

… … We have log(a) = log(b) so a = b

… … $(x-1)(x+2)=(6x-8)$

… … $x^2+x-2=6x-8$

… … $x^2-5x+6=0$

… … $(x-3)(x-2)=0$

… … hence

… … $x=2$ .. or .. $x = 3$

… … Can we accept both solutions?

… … log(y) is only defined when y > 0

… … Go back to the original question.

… … For each value of x the term inside each log must be positive:

… … Is x – 1 > 0?

… … … … when x = 2, yes!
… … … … when x = 3, yes!

… … Is x + 2 > 0 ?

… … … … when x = 2, yes!
… … … … when x = 3, yes!

… … Is 6x – 8 > 0?

… … … … when x = 2, yes!
… … … … when x = 3, yes!

… … In this case, this is true for 2 and 3 so accept both answers.

… … Solution is $x = \{2, \; 3\}$

.

Unless otherwise stated, the content of this page is licensed under Creative Commons Attribution-ShareAlike 3.0 License